Genetic predisposition in anti‐LGI1 and anti‐NMDA receptor encephalitis. Issue 4 (23rd April 2018) - Mueller, Stefanie H.; Färber, Anna; Prüss, Harald; Melzer, Nico; Golombeck, Kristin S.; Kümpfel, Tania; Thaler, Franziska; Elisak, Martin; Lewerenz, Jan; Kaufmann, Max; Sühs, Kurt‐Wolfram; Ringelstein, Marius; et al.
Abstract : We performed a genome‐wide association study in 1, 194 controls and 150 patients with anti‐ N ‐methyl‐D‐aspartate receptor (anti‐NMDAR, n = 96) or anti‐leucine‐rich glioma‐inactivated1 (anti‐LGI1, n = 54) autoimmune encephalitis. Anti‐LGI1 encephalitis was highly associated with 27 single‐nucleotide polymorphisms (SNPs) in the HLA‐II region (leading SNP rs2858870 p = 1.22 × 10 −17, OR = 13.66 [7.50–24.87]). Potential associations, below genome‐wide significance, were found with rs72961463 close to the doublecortin‐like kinase 2 gene ( DCLK2 ) and rs62110161 in a cluster of zinc‐finger genes. HLA allele imputation identified association of anti‐LGI1 encephalitis with HLA‐II haplotypes encompassing DRB1*07:01, DQA1*02:01 and DQB1*02:02 ( p < 2.2 × 10 −16 ) and anti‐NMDAR encephalitis with HLA‐I allele B*07:02 ( p = 0.039). No shared genetic risk factors between encephalitides were identified. Ann Neurol 2018;83:863–869